Code Switching and Code Mixing Used by Students in Social Media - Hayati, Rizka; Anindhita, Widyashanti Kunthara (LPPM Universitas Pekalongan, 2024)
Bilingual students often use code switching and code mixing in their communication specially in social media. Code switching and code mixing are the language phenomena in which the speakers mix language in their communication The objective of this study is to find out the code switching and code mixing used by students in their written language in social media. The result shows that students often used code switching and code mixing in their social media, the mixing and switching involve the use English, Indonesian, and Javanese.